Habilitation provision for children and young people with vision impairment in the United Kingdom: A lack of clarity leading to inconsistencies. (January 2017) - Hogg, Kat; Thetford, Clare; Wheeler, Sara Louise; York, Sarah; Moxon, Rachel; Robinson, Jude
The key to empowering and supporting children and young people (CYP) with vision impairment (VI) to achieve their potential lies in the delivery of habilitation training. Evidence has revealed that provision of habilitation services across the United Kingdom was inconsistent, with CYP with VI not receiving services in some areas. This research explored the accessibility and quality of habilitation provision for CYP with VI via two studies: (1) 12 qualitative case studies of habilitation practice and (2) surveys of habilitation training experiences, with CYP with VI ( n = 43) and with parents of CYP with VI ( n = 68). Five themes were identified highlighting inconsistencies and variability in the delivery of habilitation training in recent years, a lack of focus on independent living skills training, on social inclusion and emotional well-being, a lack of support for parents and a lack of clarity with regard to the definition of habilitation, and who is responsible for providing training.